2000
DOI: 10.1002/(sici)1097-0134(20000301)38:4<393::aid-prot5>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor CopR: Structure model-based localization of the deoxyribonucleic acid binding motif

Abstract: The plasmid pIP501 encoded transcriptional repressor CopR is one of the two regulators of plasmid copy number. CopR binds as a dimer to a nearly palindromic operator with the consensus sequence 5'-CGTG. Intermediate sequence searches revealed a significant structural relationship between CopR and the bacteriophage P22 c2 and the 434 c1 repressors. In this report we describe the experimental verification of a CopR homology model, which is based on a fairly low-sequence identity of 13.8% to P22 c2 repressor. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The steps involved in the prediction of protein structure by homology modeling. Structure modeling of the bacterial transcriptional repressor CopR is shown [28]. Although the model is based on a low-sequence identity of only 13.8% between CopR and the P22 c2 repressor, several experimental methods support this homology model.…”
Section: Experimental Protein Structure Information and The Sequence-mentioning
confidence: 96%
See 1 more Smart Citation
“…The steps involved in the prediction of protein structure by homology modeling. Structure modeling of the bacterial transcriptional repressor CopR is shown [28]. Although the model is based on a low-sequence identity of only 13.8% between CopR and the P22 c2 repressor, several experimental methods support this homology model.…”
Section: Experimental Protein Structure Information and The Sequence-mentioning
confidence: 96%
“…Typically, the amino acids that are to be modified in these studies are selected on the basis of sequence alignments by focusing on conserved residues. However, if at least some structure information is available, the selection of the amino acids that are to be mutated can be much more precise and successful [28]. This approach is even more powerful when applied in conjunction with pharmacologically active compounds.…”
Section: Structure-guided Design Of Mutagenesis Experimentsmentioning
confidence: 99%
“…2), termed KS9, had been analyzed previously (28) and was found to be bound at least as efficiently as the wild-type sequence. Our three-dimensional model of the N-terminal 63 amino acids of CopR (30) predicts that this nucleotide position in binding site I is contacted by R34 of the recognition helix (Fig. 2) and that the contact would be stronger with a C instead of a T.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, it was found that CopR binds exclusively as a dimer, and the equilibrium dissociation constants for the CopR dimers and the CopR-DNA complex were calculated to be 0.4 nM and 1.4 M, respectively (29). A three-dimensional model of the Nterminal 63 amino acids of CopR was built and was used to identify amino acids involved in DNA binding and dimerization (30,31,32). By this means, it was found that amino acids R29 and R34, located in the recognition helix (helix III) of the helix-turn-helix motif, make specific contacts to the DNA at G240 (binding site I) and G254 (binding site II) or G242/T243 (site I) and G251 (site II), respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation